Identification of a Subset of Human Immunodeficiency Virus Type 1 (HIV-1), HIV-2, and Simian Immunodeficiency Virus Strains Able To Exploit an Alternative Coreceptor on Untransformed Human Brain and Lymphoid Cells - Willey, Samantha J. (American Society for Microbiology, 2003)
The chemokine receptors CCR5 and CXCR4 are the major coreceptors for human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV). At least 12 other chemokine receptors or close relatives support infection by particular HIV and SIV strains on CD4(+) transformed indicator cell lines in vitro. However, the role of these alternative coreceptors in vivo is presently thought to be insignificant. Infection of cell lines expressing high levels of recombinant CD4 and coreceptors thus does not provide a true indication of coreceptor use in vivo. We therefore tested primary untransformed cell cultures that lack CCR5 and CXCR4, including astrocytes and brain microvascular endothelial cells (BMVECs), for naturally expressed alternative coreceptors functional for HIV and SIV infection. An adenovirus vector (Ad-CD4) was used to express CD4 in CD4(−) astrocytes and thus confer efficient infection if a functional coreceptor is present. Using a large panel of viruses with well-defined coreceptor usage, we identified a subset of HIV and SIV strains able to infect two astrocyte cultures derived from adult brain tissue. Astrocyte infection was partially inhibited by several chemokines, indicating a role for the chemokine receptor family in the observed infection. BMVECs were weakly positive for CD4 but negative for CCR5 and CXCR4 and were susceptible to infection by the same subset of isolates that infected astrocytes. BMVEC infection was efficiently inhibited by the chemokine vMIP-I, implicating one of its receptors as an alternative coreceptor for HIV and SIV infection. Furthermore, we tested whether the HIV type 1 and type 2 strains identified were able to infect peripheral blood mononuclear cells (PBMCs) via an alternative coreceptor. Several strains replicated in Δ32/Δ32 CCR5 PBMCs with CXCR4 blocked by AMD3100. This AMD3100-resistant replication was also sensitive to vMIP-I inhibition. The nature and potential role of this alternative coreceptor(s) in HIV infection in vivo is discussed.